Sustained high glucose intake accelerates type 1 diabetes in NOD mice - Li, Xiangqian; Wang, Lina; Meng, Gang; Chen, Xiaoling; Yang, Shushu; Zhang, Mengjun; Zheng, Zhengni; Zhou, Jie; Lan, Zhu; Wu, Yuzhang; Wang, Li (Frontiers in Endocrinology, 2022)
The incidence of type 1 diabetes (T1D) has increased too rapid over the past three decades, supporting the role of environmental factors. Epidemiological studies have suggested that dietary factors, especially high consumption of high glycaemic index carbohydrates and sugars, may trigger or exacerbate T1D process. In this study, we aimed to provide experimental evidence to confirm this relevance and to explore the underlying mechanisms. The results indicated that sustained high glucose drinking significantly aggravates islet inflammation and accelerates the onset of type 1 diabetes in NOD mice. Mechanistically, high glucose treatment induces aberrant ER stress and up-regulates the expression of autoantigens in islet beta cell. Moreover, high glucose treatment alters the proteome of beta-cells-derived small extracellular vesicles (sEV), and significantly enhances the ability of sEV to promote DC maturation and stimulate immune inflammatory response. Therefore, avoiding high sugar intake may be an effective disease prevention strategy for children or adults susceptible to type 1 diabetes.